2009
DOI: 10.1159/000218533
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Body Mass Index on Operability, Morbidity and Disease Outcome following Radical Cystectomy

Abstract: Introduction: Obesity may influence postoperative outcome after tumor surgery. We evaluated the impact of patients’ body mass index (BMI) on peri- and postoperative morbidity and outcome following radical cystectomy for bladder cancer. Patients and Methods: 390 consecutive patients who underwent radical cystectomy due to bladder cancer from January 1986 to December 2004 were reviewed. According to WHO criteria, patients were divided into normal weight (NW, 45.6%), overweight (OW, 44.4%) and obese (10.0%) subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 40 publications
0
43
1
Order By: Relevance
“…13 However, other studies did not find a correlation between obesity and bladder cancer. 9,12 In the present study, overweight and obese patients who underwent radical cystectomy for MIBC had more favorable pathological features and a better prognosis than those with normal BMI values. Furthermore, the results of multivariable analysis showed that a low BMI is a significant factor of poor prognosis compared with other clinicopathological factors.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…13 However, other studies did not find a correlation between obesity and bladder cancer. 9,12 In the present study, overweight and obese patients who underwent radical cystectomy for MIBC had more favorable pathological features and a better prognosis than those with normal BMI values. Furthermore, the results of multivariable analysis showed that a low BMI is a significant factor of poor prognosis compared with other clinicopathological factors.…”
Section: Discussionmentioning
confidence: 46%
“…9 For example, increased BMI is associated with increased operative times, blood loss and perioperative complications compared with those in patients with normal weight. 10 However, in the present study, we found no differences in the 90-day mortality rate according to BMI category, which showed that obesity had no effect on the incidence of perioperative complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reyes et al 33 found that tract infections, pyelonephritis, wound infections and overall complications were less frequent in normal-weight patients (18.5-24.9kg/m 2 ) compared to overweight (25-29.9kg/m 2 ) and obese (≥30.0kg/m 2 ) patients. BMI was not a predictor of mortality and complication development after RC in the Maurer et al 35 study, except for postoperative bleeding, which was more frequent in subjects with a high BMI. Compared to subjects with a BMI of 18-25kg/m 2 , subjects with a BMI >30kg/m 2 had a higher risk of cancer-specific mortality 38,42 , incisional hernia 40 , re-admission 30d and 90d after RC 39 , ileus 36 , parastomal hernia 45 and deep venous thrombosis 43,44 .…”
Section: Body Mass Indexmentioning
confidence: 72%
“…Twelve studies investigated the association between BMI and RC outcomes [33][34][35][36][37][38][39][40][41][42][43][44] . Reyes et al 33 found that tract infections, pyelonephritis, wound infections and overall complications were less frequent in normal-weight patients (18.5-24.9kg/m 2 ) compared to overweight (25-29.9kg/m 2 ) and obese (≥30.0kg/m 2 ) patients.…”
Section: Body Mass Indexmentioning
confidence: 99%